2008
DOI: 10.3844/ajassp.2008.1167.1174
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Decentralized Load Frequency Control Using HPSO Algorithms in Deregulated Power Systems

Abstract: Load Frequency Control (LFC) is one the most important issues in electrical power system design/operation and is becoming much more significant recently with increasing size, changing structure and complexity in interconnected power systems. In practice LFC systems use simple Proportional-Integral (PI) or Integral (I) controllers. However, since the PI or I control parameters are usually tuned based on classical or trial-and-error approaches, they are incapable of obtaining good dynamic performance for various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 28 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…Particle swarm optimization (PSO) algorithm has been used by Ghoshal [13] to optimize fuzzy-logic based proportional-integral-derivative (PID) controller gains in view of AGC study of power system. Also, variants of PSO have been proposed to optimize the controller gain(s) for AGC problem of multi-area power system [14][15][16][17]. The utilization of artificial bee colony algorithm in AGC study of an interconnected power system may be found in [18].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle swarm optimization (PSO) algorithm has been used by Ghoshal [13] to optimize fuzzy-logic based proportional-integral-derivative (PID) controller gains in view of AGC study of power system. Also, variants of PSO have been proposed to optimize the controller gain(s) for AGC problem of multi-area power system [14][15][16][17]. The utilization of artificial bee colony algorithm in AGC study of an interconnected power system may be found in [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The OLTF for reheat turbine unit may be expressed by (15). The transfer function blocks for electric hydro governor (having transfer functionḠ g (s)) and hydro turbine (having transfer function (Ḡ t (s))) system may be stated by (16) and (17), respectively:…”
Section: Area-1mentioning
confidence: 99%
“…To evaluate the performance of a LFC mechanism, two objective functions, including integral of time multiplied absolute value of the error (ITAE) and figure of demerit (FD), are usually considered in the literature, which are as follows [11,12,[55][56][57][58]:…”
Section: Figurementioning
confidence: 99%
“…In (20), w is the weight parameter that weighs OS and US (in terms of signal magnitude) versus ST (in terms of time). The well-known two-area power system, usually used as test case in LFC research works [11,12,[55][56][57][58], is considered as test system here. Also, large variations in the load of the areas are applied as disturbance to the system.…”
Section: Figurementioning
confidence: 99%
“…Authors in [7] say that GA optimized based upon fuzzy gain scheduling for conventional PI controller. Two area thermal power system for composition of a hybrid PSO algorithm optimizing for the gain scheduling of PI controller shown by Taher in 2008 [8]. Design of AGC regulator that deals with numerous system aspects depicts in the literature by Pothiya et al in ref.…”
Section: Literature Surveymentioning
confidence: 99%